Role of Ag nanoparticles embedded on optical, photoluminescence and elastic properties of samarium magnesium borotellurite glass system - Mohd Azlan Nafiah (Tanjung Malim, 2023)
Role of Ag nanoparticles embedded on optical, photoluminescence and elastic properties of samarium magnesium borotellurite glass system by Mohd Azlan Nafiah